Desenterrando os mortos e enterrando os vivos em suas entranhas : uma história social dos sapes na Serra Leoa (1506-1615) - Roberth Daylon dos Santos Freitas (2022)
The purpose of this work is to provide a social history of the sapes of Sierra Leone in the sixteenth and seventeenth centuries. To this end, travel accounts by Europeans and Cape Verdeans were used as primary sources of information about the region and its inhabitants. In an attempt to overcome a history of great deeds and great African personalities, this study approaches a theoretical and methodological corpus of social history and seeks to understand the Sapes through their systems of order and the expression of these systems in everyday life. To this end, the ritual practices and religious ceremonies of the sapes, their legal and political customs, the production and exchange of products between the group and its neighbors, and the relationships they established with the spirits of the land and territory were analyzed.There is a tendency to study the sapes from the Mane-Sumba expansion, a demographic movement of a group associated with the Mali Empire. The name of the expansion was due to the fact that the invaders were called manes and the peoples incorporated by this army earned the nickname "sumba" for their practice of anthropophagy. To counter this trend we investigate such conflicts as a key moment of articulation between groups and systems of order in contact. We conclude that by changing the focus of analysis and making a social history of the sapes we realize their importance to the History of Sierra Leone and Senegambia and thus tension historiography and complexify narratives about the region and the Mane-Sumba Expansion.